2010
DOI: 10.1212/wnl.0b013e3181ed9e96
|View full text |Cite
|
Sign up to set email alerts
|

Severe neonatal episodic laryngospasm due to de novo SCN4A mutations

Abstract: Severe neonatal episodic laryngospasm is a new phenotype caused by a sodium channelopathy, which can be alleviated by channel blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 10 publications
0
61
0
Order By: Relevance
“…One infant who was not treated in time with either carbamazepine or mexiletine died due to respiratory arrest during an apneic episode. A de novo A799S missense mutation of the Na v 1.4 channel was found in this patient (Lion-Francois et al, 2010; Simkin et al, 2011). This mutation is located on the S6 transmembrane segment of domain II and results in such a severe phenotype by shifting the steady state of activation in a hyperpolarizing direction, slowing the kinetics of fast inactivation and deactivation, and dramatically increasing channel open probability (Simkin et al, 2011).…”
Section: Skeletal Muscle Pathophysiologymentioning
confidence: 75%
See 1 more Smart Citation
“…One infant who was not treated in time with either carbamazepine or mexiletine died due to respiratory arrest during an apneic episode. A de novo A799S missense mutation of the Na v 1.4 channel was found in this patient (Lion-Francois et al, 2010; Simkin et al, 2011). This mutation is located on the S6 transmembrane segment of domain II and results in such a severe phenotype by shifting the steady state of activation in a hyperpolarizing direction, slowing the kinetics of fast inactivation and deactivation, and dramatically increasing channel open probability (Simkin et al, 2011).…”
Section: Skeletal Muscle Pathophysiologymentioning
confidence: 75%
“…Recently a novel Na v 1.4 myotonia mutation was identified causing severe neonatal episodic laryngospasm (SNEL) found to be lethal in newborns (Lion-Francois et al, 2010). These newborns presented with episodic apneas and apparent life threatening events that included myotonia of the laryngeal muscles preventing proper ventilation.…”
Section: Skeletal Muscle Pathophysiologymentioning
confidence: 99%
“…Recently, severe neonatal episodic laryngospasm, a form of life-threatening myotonia, has been associated with SCN4A mutations (G1306E, T1313M and A799S) 51 52. Functional work via patch-clamp techniques showed that the A799S mutation promoted the channel open state with sustained activity leading to hyperexcitability of laryngeal muscles which could be lethal during infancy 52…”
Section: Subsectionsmentioning
confidence: 99%
“…The extreme cramps in the tongue muscles are also peculiar . Myotonia in the tongue muscles is well known, but impressive painful cramps and contraction, as seen in these patients, have not been recognized.…”
Section: Discussionmentioning
confidence: 99%